The City as Campus : Urbanism and Higher Education in Chicago - Haar, Sharon, 1962- (Book collections on Project MUSE., 2011)
Urban schools play an important role in shaping the cities outside their walls. This book uses Chicago as a case study to examine how universities interact with their urban contexts, demonstrating how higher education became integrated with ideas of urban growth as schools evolved alongside the city. The book shows the strain of this integration, detailing historical accounts of battles over space as campus designers faced the challenge of weaving the social, spatial, and architectural conditions of the urban milieu into new forms to meet the changing needs of academia.